Structure of human O-GlcNAc transferase and its complex with a peptide substrate - Lazarus, Michael B.; Nam, Yunsun; Jiang, Jiaoyang; Sliz, Piotr; Walker, Suzanne (Nature (London), 2011)
Structure of a nutrient sensor O -GlcNAc transferase (OGT) is an essential mammalian enzyme that acts as a nutrient sensor. It glycosylates proteins with O -linked β- N -acetylglucosamine ( O -GlcNAc), and this regulates a variety of cellular signalling pathways. Suzanne Walker and colleagues present the crystal structure of human OGT as a binary complex with UDP and as a ternary complex with UDP and a peptide substrate. The structures show how OGT recognizes peptide sequences, and provide information on the mechanism of action of an enzyme that has been found in aberrant form in a number of human conditions including diabetes, cancer and Alzheimer's disease. O GlcNAc transferase (OGT) is an essential mammalian enzyme that glycosylates proteins with O-linked β- N -acetylglucosamine ( O -GlcNAc), and this regulates a variety of cellular signalling pathways. Here, the crystal structure of human OGT as a binary complex with UDP and a ternary complex with UDP and a peptide substrate is presented. The structures show how OGT recognizes peptide sequences and provide information on the enzymatic mechanism. The essential mammalian enzyme O-linked β- N -acetylglucosamine transferase ( O -GlcNAc transferase, here OGT) couples metabolic status to the regulation of a wide variety of cellular signalling pathways by acting as a nutrient sensor 1 . OGT catalyses the transfer of N -acetylglucosamine from UDP- N -acetylglucosamine (UDP-GlcNAc) to serines and threonines of cytoplasmic, nuclear and mitochondrial proteins 2 , 3 , including numerous transcription factors 4 , tumour suppressors, kinases 5 , phosphatases 1 and histone-modifying proteins 6 . Aberrant glycosylation by OGT has been linked to insulin resistance 7 , diabetic complications 8 , cancer 9 and neurodegenerative diseases including Alzheimer’s 10 . Despite the importance of OGT, the details of how it recognizes and glycosylates its protein substrates are largely unknown. We report here two crystal structures of human OGT, as a binary complex with UDP (2.8 Å resolution) and as a ternary complex with UDP and a peptide substrate (1.95 Å). The structures provide clues to the enzyme mechanism, show how OGT recognizes target peptide sequences, and reveal the fold of the unique domain between the two halves of the catalytic region. This information will accelerate the rational design of biological experiments to investigate OGT’s functions; it will also help the design of inhibitors for use as cellular probes and help to assess its potential as a therapeutic target.